Analysis of Discourse Deixis in EFL Learners of STIBA Persada Bunda - Maspufah Maspufah (ELT-Lectura, 2018)
Discourse deixis is one type of deixis which its interpretation depends greatly to the context surround it. This research was intended to find out the students’ competence in interpreting discourse deixis in narrative text This research is a descriptive research. Fifteen students of third semester students of 2017/2018 Academic Year of STIBA Persada Bunda were taken as the subject of the research. The instruments used to collect the data were quantitative and qualitative data. The quantitative data was in the form of reading tests. The qualitative data were in the form of interview. From the finding of the research, it was found that: (1) The students’ ability in interpreting discourse deixis in narrative text was in good category. (2) They had problem with the context, situational, and vocabulary. Thus, it can be concluded that the students’ ability in interpreting discourse deixis in narrative text needed to be improved because they still had limited vocabulary and low understanding of context.